Potentiometric and NMR spectroscopic study of protonations and amide hydrogen exchange rates of DTPA-bis(butylamide), DTPA-bis(glucamide), and their lanthanide(III) complexes - Lammers, Hendrik (1998)
The macroscopic and microscopic protonations of DTPA-GlucA2 (DTPA-bis(glucamide)) have been investigated using potentiometry, 1H and 13C NMR. The protonation behavior appears to be similar to that of the corresponding bis(alkylamides), showing that it is not affected by the presence of the polyhydroxy side chains. Consideration of the various possible protonation pathways leads to the conclusion that the differences in basicity of the amino functions in DTPA and DTPA-bis(amides) result in different protonation sequences of these ligands, which is reflected in the macroscopic protonation constants. The significance for the design of DTPA-based contrast agents for MRI is discussed. Exchange rates of the amide NH of this compound and that of DTPA-bis(butylamide) (DTPA-BuA2) were determined via longitudinal relaxation rate measurements of the amide 1H resonances in H2O---D2O (9:1) as solvent. The reaction is strongly base catalyzed and the rate increases substantially upon coordination of the DTPA-bis(amide) by La(III).